Investigation of Heterologously Expressed Glucose-6-Phosphate Dehydrogenase Genes in a Yeast zwf1 Deletion - Heinisch, Jürgen J. (Microorganisms, 2020)
Glucose-6-phosphate dehydrogenase (G6PD) is a key enzyme of the oxidative part of the pentose phosphate pathway and serves as the major source of NADPH for metabolic reactions and oxidative stress response in pro- and eukaryotic cells. We here report on a strain of the model yeast Saccharomyces cerevisiae which lacks the G6PD-encoding ZWF1 gene and displays distinct growth retardation on rich and synthetic media, as well as a strongly reduced chronological lifespan. This strain was used as a recipient to introduce plasmid-encoded heterologous G6PD genes, synthesized in the yeast codon usage and expressed under the control of the native PFK2 promotor. Complementation of the hypersensitivity of the zwf1 mutant towards hydrogen peroxide to different degrees was observed for the genes from humans (HsG6PD1), the milk yeast Kluyveromyces lactis (KlZWF1), the bacteria Escherichia coli (EcZWF1) and Leuconostoc mesenteroides (LmZWF1), as well as the genes encoding three different plant G6PD isoforms from Arabidopsis thaliana (AtG6PD1, AtG6PD5, AtG6PD6). The plastidic AtG6PD1 isoform retained its redox-sensitive activity when produced in the yeast as a cytosolic enzyme, demonstrating the suitability of this host for determination of its physiological properties. Mutations precluding the formation of a disulfide bridge in AtG6PD1 abolished its redox-sensitivity but improved its capacity to complement the yeast zwf1 deletion. Given the importance of G6PD in human diseases and plant growth, this heterologous expression system offers a broad range of applications.